FINANCIAL ANALYSIS INSPIRED BY THE 5P APPROACH OF SUSTAINABLE DEVELOPMENT APPLIED TO THE NASDAQ INDEX - JOSÉ GERARDO DE LA VEGA MENESES (Innovare Journal of Agricultural Sciences, 2025)
In this document, the research problem of proposing a methodology to apply financial analysis under the 5P approach of Sustainable Development: People, Prosperity, Peace, Planet, and Partnerships was addressed. To do this, the financial information of companies that make up the Nasdaq Index was used to design indicators that plausibly refer to sustainable development. The methodology used in this research was quantitative, documentary, and descriptive. Financial indicators that are relevant to the sustainable development of entities were strategically selected, and their results were quantitatively analyzed, normalized to propose a methodology to identify, through financial ratios, the degree of sustainable development in important companies of the Nasdaq Index. This document aims to motivate the replication of this type of financial analysis to deepen the financial analysis inspired by the sustainable development approach, as part of the fundamental analysis applied to companies listed on stock exchanges.